2019
DOI: 10.1108/jpmh-10-2018-0069
|View full text |Cite
|
Sign up to set email alerts
|

Clinical depression moderates effects of animal-assisted stress prevention program on college students’ emotion

Abstract: Purpose The purpose of this paper is to examine whether clinical levels of depression moderated university students’ momentary emotional states (e.g. feeling content, anxious, irritable and depressed) in response to conditions commonly experienced during universal, college-based Animal Visitation Programs (AVPs). Design/methodology/approach During a real-life efficacy trial, students (N = 192) were randomly assigned to three common AVP conditions: a hands-on condition in which participants could freely pet c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 18 publications
1
34
0
Order By: Relevance
“…Few studies have examined the moderating effects of students' mood-related risk status on the efficacy of college-based AAAs. Exceptions are results by Pendry, Vandagriff, and Carr [32], who showed that clinically depressed students reported significantly higher levels of momentary negative emotion including irritability, depression, and anxiety after waiting in line for their turn to engage in hands-on petting of shelter cats and dogs compared to nondepressed students. Similarly, recent findings showed that students who had experienced a mental health problem, learning disability, suicidal ideation, or academic failure experienced significant improvement in aspects of Executive Functioning (EF) after attending four weekly, hour-long sessions focused on interacting with therapy dogs and their handlers, whereas students without such risk factors or those who received traditional evidence-based stress management lectures did not experience such improvements.…”
Section: Moderation Of Risk Statusmentioning
confidence: 81%
See 2 more Smart Citations
“…Few studies have examined the moderating effects of students' mood-related risk status on the efficacy of college-based AAAs. Exceptions are results by Pendry, Vandagriff, and Carr [32], who showed that clinically depressed students reported significantly higher levels of momentary negative emotion including irritability, depression, and anxiety after waiting in line for their turn to engage in hands-on petting of shelter cats and dogs compared to nondepressed students. Similarly, recent findings showed that students who had experienced a mental health problem, learning disability, suicidal ideation, or academic failure experienced significant improvement in aspects of Executive Functioning (EF) after attending four weekly, hour-long sessions focused on interacting with therapy dogs and their handlers, whereas students without such risk factors or those who received traditional evidence-based stress management lectures did not experience such improvements.…”
Section: Moderation Of Risk Statusmentioning
confidence: 81%
“…a planned and goal-oriented informal interaction or visitation conducted by the human-animal team for motivational, educational and recreational purposes." Conceptualized as preventive interventions to promote students' general well-being, nearly 1,000 U.S. College campuses [22,23] conduct AAAs within the context of Animal Visitation Programs (AVPs), which are campus-based visitation programs providing university students with the opportunity to interact with animals on a one-time, drop-in basis.…”
Section: Campus-based Animal Assisted Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, we focused on assessing stress using physiological parameters of heart rate and blood pressure. At the same time, mood and stress were subjectively evaluated using the Likert scale, similar to the study of Pendry et al 2018 [37].…”
Section: Discussionmentioning
confidence: 99%
“…Animal-assisted activities (AAAs), or activities that incorporate human animal interaction to promote student well-being, have grown increasingly popular on university campuses to combat high student stress levels [1]. While initial evidence suggests positive outcomes for student participants, including reduced perceived stress [2], positive changes in mood [3,4,5] and reductions in student cortisol levels [6], there is limited research on the nature of human animal interactions during university-based AAAs. There appears to be no research on the extent to which dyadic functioning between handler and dog is manifested during university-based AAAs, nor do we have knowledge about the extent to which dyadic functioning between handler and animal may relate to triadic contexts, such as when handlers and dog teams engage with students.…”
Section: Introductionmentioning
confidence: 99%